First observation of a nuclear s-state of a $Ξ$ hypernucleus, $^{15}_{Ξ}{\rm C}$. (22nd July 2021) - Yoshimoto, M; Ahn, J K; Bassalleck, B; Ekawa, H; Endo, Y; Fujita, M; Han, Y; Hashimoto, T; Hayakawa, S H; Hicks, K; Hoshino, K; Hoshino, S; et al.
Abstract: Bound systems of $Ξ^-$ –$^{14}_{}{\rm N}$ are studied via $Ξ^-$ capture at rest followed by emission of a twin single-$Λ$ hypernucleus in the emulsion detectors. Two events forming extremely deep $Ξ^-$ bound states were obtained by analysis of a hybrid method in the E07 experiment at J-PARC and reanalysis of the E373 experiment at KEK-PS. The decay mode of one event was assigned as $Ξ^-+^{14}\!\, \!\!{\rm N}→^{5}_{Λ}\!\!\!{\rm He} + ^{5}_{Λ}\!\!{\rm He} + ^{4}\!\!{\rm He} + n$ . Since there are no excited states for daughter particles, the binding energy of the $Ξ^-$ hyperon, $B_{Ξ^-}$, in the $^{14}_{}{\rm N}$ nucleus was uniquely determined to be $6.27 ± 0.27$ MeV. Another $Ξ^-$ –$^{14}_{}{\rm N}$ system via the decay $^{9}_{Λ}{\rm Be} + ^{5}_{Λ}\!\!\!{\rm He} + n$ brings a $B_{Ξ^-}$ value, $8.00 ± 0.77$ MeV or $4.96 ± 0.77$ MeV, where the two possible values of $B_{Ξ^-}$ correspond to the ground and the excited states of the daughter $^{9}_{Λ}{\rm Be}$ nucleus, respectively. Because the $B_{Ξ^-}$ values are larger than those of the previously reported events (KISO and IBUKI), which are both interpreted as the nuclear $1p$ state of the $Ξ^-$ –$^{14}_{}{\rm N}$ system, these new events give the first indication of the nuclear $1s$ state of the $Ξ$ hypernucleus, $^{15}_{Ξ}{\rm C}$ .